High-performance thin-film transistors with solution-processed ScInO channel layer based on environmental friendly precursor. (31st August 2017) - Song, Wei; Lan, Linfeng; Li, Meiling; Wang, Lei; Lin, Zhenguo; Sun, Sheng; Li, Yuzhi; Song, Erlong; Gao, Peixiong; Li, Yan; Peng, Junbiao
Abstract: Thin-film transistors (TFTs) with solution-processed scandium (Sc) substituted indium oxide (Sc x In1− x O3, ScInO) thin films based on environmental friendly water-induced precursor were fabricated. As the Sc concentration increases from 0% to 10%, the mobility decreases from 23.7 cm 2 V −1 s −1 to 6.4 cm 2 V −1 s −1, which is attributed to the non-overlapping of the Sc 3+ electron orbit. However, the off current decreases and the turn-ON voltage ( V ON ) shifts towards the positive direction as the Sc content increases, which indicates lower carrier density after incorporation of Sc into In2 O3 . More interestingly, the incorporation of Sc into In2 O3 can effectively improve the electrical stability of the TFT devices under gate bias stress, which is attributed to the reduction of the number of oxygen vacancies due to the relatively low standard electrode potential (−2.36) of Sc and strong bonding strength of Sc–O (680 kJ mol −1 ). The reduction of oxygen vacancies is confirmed by the x-ray photoelectron spectroscopy (XPS) experiments.